Phenotypic and Genomic Identification of Glyphosate-Herbicide Degrading Bacterial Isolate From the Rhizosphere of Chilli Pepper - Maulida, Khilma Ziyadatur Rizka; Lisdiana, Lisa (LenteraBio : Berkala Ilmiah Biologi, 2024)
Bacteria are one of the bioremediation agents to treat pollution in agricultural land. Bacteria can degrade contaminant compounds. Bacterial isolate CF6 is a rhizosphere bacterial isolate from chili pepper agricultural soil which has the potential to degrade glyphosate herbicide. However, it needs to be identified to be applied as a bioremediation agent and its effects on the ecosystem understood. This research aims to identify phenotypically and genomically isolates of rhizosphere bacteria that have the potential to degrade glyphosate herbicides so that they can be applied further. Phenotypic identification methods consisted of motility tests, gram staining, catalase, citrate, urease, endospores, Voges-Proskauer, indole production, methyl red, growth in 5% NaCl, and sugar reduction tests. The genomic identification method was divided into four stages, namely DNA isolation, 16S rRNA gene amplification, electrophoresis, and 16S rRNA gene sequencing. Data from phenotypic and genomic tests were analyzed numerically using NTSys 2.11a and MEGA11, respectively. The dendrogram results in this study showed that the CF6 bacterial isolate belonged to the same clade as bacteria of the genus Klebsiella. Meanwhile, the results of BLASTn analysis showed that the CF6 test isolate had a 16S rRNA gene sequence similarity with Klebsiella quasipneumoniae of 98.62%. From the results of the two identification methods, it can be concluded that the CF6 bacterial isolate is K. quasipneumoniae. Aspects of pathogenicity and bacterial degradation rate need to be tested before implementation.